(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the role of information technology in enhancing mathematical problem-solving competencies. This study uses a qualitative approach with a case study type. The subjects of this research include teachers and students who are directly involved in digital-based mathematics learning using instructional videos. Data collection techniques were conducted through semi-structured interviews, data analysis, and documentation. Data analysis was carried out through several stages including data reduction, data presentation, and conclusion drawing. The results of the analysis show that digital transformation in mathematics learning, particularly through the use of digital media such as learning videos on YouTube, can enhance students’ understanding of concepts and their ability to solve mathematical problems, especially on topics that require visualization such as gradients. Although information technology offers various advantages, such as ease of access to learning and more engaging material presentation, its success is still influenced by factors such as the availability of devices, internet connectivity, student motivation, and the active role of teachers in providing guidance and encouragement. Thus, the success of integrating technology in mathematics learning heavily relies on the combination of appropriate digital media, adequate infrastructure support, and consistent teacher mentoring.